2009
DOI: 10.1016/j.ejvs.2008.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Dutch Translated Aberdeen Varicose Vein Questionnaire

Abstract: This study supports applications of the Dutch AVVQ in HR-QOL measurement in patients with venous disease in the Netherlands and the Flemish speaking part of Belgium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 8 publications
(10 reference statements)
5
33
1
Order By: Relevance
“…The correlations between the AVVQ and the SF-36 indicate the validity of the total score of the AVVQ and its Pain and Dysfunction domain, with a significant negative relationship between these values and all SF-36 domains, considered of reasonable to good magnitude, and with their largest correlations with the SF-36 domains Functional Capacity (r=-0506, p<0.01), Role -Physical (r=-0.521; p<0.01) and Pain (r= -0.547; p<0.01), in common with results reported by Klem et al 30 and confirmed by Garrat et al 14 in a study of the original version. These correlations suggest that the AVVQ captures the adverse effects of CVD in all SF-36 domains.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The correlations between the AVVQ and the SF-36 indicate the validity of the total score of the AVVQ and its Pain and Dysfunction domain, with a significant negative relationship between these values and all SF-36 domains, considered of reasonable to good magnitude, and with their largest correlations with the SF-36 domains Functional Capacity (r=-0506, p<0.01), Role -Physical (r=-0.521; p<0.01) and Pain (r= -0.547; p<0.01), in common with results reported by Klem et al 30 and confirmed by Garrat et al 14 in a study of the original version. These correlations suggest that the AVVQ captures the adverse effects of CVD in all SF-36 domains.…”
Section: Discussionsupporting
confidence: 78%
“…This possibly occurred because the participants were not classified separately by C4 subcategory (C4a and C4b), in order to reproduce the procedure used in validation of the original, and also because of the static nature of the CEAP in classes C4 and C5, interfering with assessment and complicating follow-up over time, as stated by Vasquez 34 Some authors state that the negative impact of CVD on QoL is primarily related to the domains Pain, Physical Function and Mobility. 10 In agreement with this, it was observed that all patients exhibited compromised general and specific QoL, with the greatest correlations between the AVVQ and the SF-36 occurring in the SF-36 domains Pain, Role -Physical and Functional Capacity, confirming what was reported by Garrat et al, 14 during construction of the AVVQ, and by Klem et al 30 in a later study of the clinimetric properties of their Dutch version. This provides strong evidence of its validity as a measure of QoL.…”
supporting
confidence: 77%
“…Variables were presented in means with standard deviation (SD) if distributed parametrically, or as median with the 25th and 75th percentile value (interquartile range [IQR]) if distributed nonparametrically. We compared the scores of the EuroQol quality-oflife questionnaire (EQ-5D) index and visual analog scale (VAS), 5 Aberdeen Varicose Vein Questionnaire (AVVQ), 6 and Venous Clinical Severity Score (VCSS) 7 before and 3 months after therapy using the Wilcoxon signed-rank test. We performed statistical analysis with SPSS 15.0 software (SPSS Inc, Chicago, Ill) and assigned significance at P Ͻ .05 (two-sided P).…”
Section: Pilot Studymentioning
confidence: 99%
“…20,[23][24][25][26] It consists of 12 questions and a set of mannequin legs on which participants are asked to draw their veins. Scores range from 0 to 100, with higher scores indicating a worse quality of life.…”
Section: Outcome Measuresmentioning
confidence: 99%